LATEST INSTRUMENTAL TECHNIQUES BASED ON THE USE OF A SCANNING ELECTRON MICROSCOPE FOR MINERALOGICAL ANALYSIS: APPLICATIONS IN FORENSIC SOIL ANALYSIS. PART 2: WAYS TO EXPAND THE CAPABILITIES OF SEM-BASED AUTOMATED SYSTEMS USED FOR DETERMINATION OF MINERALOGICAL COMPOSITION. SAMPLING TECHNIQUES. FACTORS LIMITING THE USE OF SUCH SYSTEMS IN FORENSIC SOIL ANALYSIS. - E. Nesterina; M. Lukashova (Теория и практика судебной экспертизы, 2014)
Novel technical decisions enabling to broad up advances of automatic mineralogical analysis on the base of scanning electron microscope are described. Sample preparation technique for this analysis is considered. The main factors which constrain the usage of this revolution method in the aid of soil and geological forensics are discussed. Examples of application the automatic mineralogical analysis on base of scanning electron microscope for objects of soil and geological nature are given.